An Evaluation of the Effect of Emotional Intelligence on Achievement Orientation in Architectural Design Education - Birer, Emel (My University, 2012)
The purpose of this study is to research the concept of achievement orientation in architecture education throughout the education periods of students, and to render the findings sharable with students and education professionals. The findings were gathered through measuring the intrinsic motivations of students in their first year of architectural education and comparing the effect of these measurement results on the students’ graduation year. The reason why the study steers towards the field of psychology is the thought that motivation is a necessary element for achieving success and affects architectural design education in a fundamental way. Motivation is a part of the emotional intelligence, an area which is now measurable in psychology.
Keywords: Architectural design education; motivation; emotional intelligence; achievement orientation